2007
DOI: 10.1111/j.1365-2583.2007.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐species transferability of microsatellite markers from six aphid (Hemiptera: Aphididae) species and their use for evaluating biotypic diversity in two cereal aphids

Abstract: The abundance and distribution of microsatellites, or simple sequence repeats (SSRs) were explored in the expressed sequence tag (EST) and genomic sequences of the pea aphid, Acyrthosiphon pisum (Harris), and the green peach aphid, Myzus persicae (Sulzer). A total of 108 newly developed, together with 40 published, SSR markers were investigated for their cross-species transferability among six aphid species. Genetic diversity among six greenbug, Schizaphis graminum (Rondani) and two Russian wheat aphid, Diurap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 67 publications
4
46
0
1
Order By: Relevance
“…Weng et al (2007) found variation in EST-derived SSRs between Biotypes 1 and 2; however, only a single clone of each biotype was assayed and the biological significance of this variation was not determined. Because D. noxia Biotypes 3, 4, and 5 were indistinguishable from Biotypes 1 and 2, it is likely they a subset of the extant population.…”
Section: Resultsmentioning
confidence: 99%
“…Weng et al (2007) found variation in EST-derived SSRs between Biotypes 1 and 2; however, only a single clone of each biotype was assayed and the biological significance of this variation was not determined. Because D. noxia Biotypes 3, 4, and 5 were indistinguishable from Biotypes 1 and 2, it is likely they a subset of the extant population.…”
Section: Resultsmentioning
confidence: 99%
“…The 10-μl PCR mix consisted of 50 mM MgCl 2 , 1.5 mM dNTPs, 0.25 μM forward primer, 1 μM reverse primer, 1 μM fluorescent dye with M13 tail, 0.45 U Promega Taq, and 10 ng genomic DNA. A single touchdown PCR procedure was set up for all primer amplifications [3,39], and the PCR reactions were performed in the Gene Amp PCR System 9700 (Applied Biosystems, Foster City, CA, USA). The PCR procedure consisted of 3 min at 95°C, followed by six cycles of 45 s at 94°C, 5 min at 68°C (with a 2°C decrease in each cycle), and 1 min at 72°C, followed by eight cycles of 45 s at 94°C, 2 min at 58°C (with a 1°C decrease in each cycle), and 1 min at 72°C, followed by 25 cycles of 45 s at 94°C, 2 min at 50°C, and 1 min at 72°C, followed by a final 7-min extension step at 72°C and stored at 4°C.…”
Section: Primers and Touchdown Pcrmentioning
confidence: 99%
“…There are previous reports of microsatellite primers cross-amplifying DNA from closely related species (Grasela andMcIntosh 2005, Kim and, or even species from a different genus (Wilson et al 2004, Weng et al 2007), but this was not observed for any of the microsatellites in the Anthonomus species tested or the more distantly related pecan weevil (Figs. 3 and 4).…”
Section: Discussionmentioning
confidence: 97%